Resolving cryptic diversity in the Chromis viridis species complex (Pomacentridae): a multilocus phylogenetic and morphometric reassessment of species boundaries - M. U. Rekha; Teena Jayakumar T. K.; Abhilash C. P.; Ahamed Rasheeq A.; Saikrishnan K. R.; Vallarasu R.; Gladston Y.; Kajal Chakraborty; Ajithkumar T. T. (Frontiers in Marine Science, 2026)
The blue-green damselfish, Chromis viridis (Cuvier, 1830), is widely distributed across Indo-Pacific coral reefs and is among the most heavily traded marine ornamental fishes. Recent molecular studies have suggested the presence of cryptic diversity within the C. viridis complex, but species boundaries remain unresolved. Multilocus phylogenetic analyses incorporating three mitochondrial markers—cytochrome c oxidase subunit I (COI), cytochrome b (cytb), and the mitochondrial control region (D-loop)—and two nuclear markers, recombination-activating gene 1 (RAG1) and recombination-activating gene 2 (RAG2), were performed to assess lineage diversification within the Chromis viridis species complex. Specimens collected from the Lakshadweep Archipelago and the Gulf of Mannar, India, formed a distinct and well-supported lineage that was clearly separated from C. viridis sensu stricto and other congeners in phylogenetic reconstructions and genetic distance analyses. Multiple species-delimitation approaches consistently supported the recognition of this lineage as an independently evolving taxon, and morphometric analyses revealed corresponding differences in body proportions and meristic characters. Based on the concordance of molecular and morphological evidence, a new species, Chromis veneta sp. nov., is herein described from the Indian Ocean. The new species differs from C. viridis in having a relatively elongate body, narrower caudal peduncle, distinctive body pigmentation, yellowish to orangish distal fin margins, and a deeply forked caudal fin with elongate lobe tips. Additional diagnostic features include differences in dentition, gill-raker counts and sagittal otolith morphology. The discovery of C. veneta sp. nov. highlights underestimated diversity within the C. viridis complex and underscores the importance of integrative taxonomy in revealing cryptic reef-fish diversity.

Impact of advanced cloud microphysics schemes for the Kerala flood events in 2018 and 2019 using the NCMRWF regional model - Rose Raphel; A. Jayakumar; T.J. Anurose; Saji Mohandas; Greeshma M. Mohan; M. Sandhya; Anumeha Dube; Donali Gogoi; V.S. Prasad; Claudio Sanchez (Atmospheric Research, 2026)

Unveiling Growth Patterns and Condition Status of 25 Flatfish Species (Order: Pleuronectiformes) from the Southern Coast of Tamil Nadu, India: Evidence from Length–Weight Relationships - R. G. Sasikumar; P. Jawahar; N. Jayakumar; G. Arul Oli; T. Ravikumar; M. Sharumathi; J. Joyson Paul; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Length–Weight Relationships and Condition Factor of Fourteen Clupeiform Fishes from the Gulf of Mannar, Southeast Coast of India - M. Armaan Arnaa; N. Jayakumar; R. Durairaja; M. Kalaiarasan; K. Karuppasamy; C. Abishek; M. Sharumathi; J. Joyson Paul; R. G. Sasikumar (Thalassas: An International Journal of Marine Sciences, 2026)

Improving lightning representation in global model through convective cloud based Price and Rind 1992 scheme - M. Sandhya; Greeshma M. Mohan; Saji Mohandas; A. Jayakumar; T.J. Anurose; V.S. Prasad (Science of The Total Environment, 2026)

Reproductive Biology and Population Dynamics of Bigeye Scad (Selar crumenophthalmus) in the Gulf of Mannar, India: Implications for Management - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; R. G. Sasikumar; K. Karuppasamy; Sanjay Chandravanshi; R. Tamilselvan (Thalassas: An International Journal of Marine Sciences, 2026)

Reproductive Traits and Population Characteristics of Atule mate (Cuvier, 1833) From the Gulf of Mannar: Implications for Minimum Legal Size - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; K. Karuppasamy; Percy Paulin J; S. Pearlin Arul Granap; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Comparative Assessment of Length-Weight Relationship and Relative Condition Factor of 25 Grouper Species along the Southern Coast of Tamil Nadu, India - J. Joyson Paul; R. Durairaja; N. Jayakumar; N. Daniel; T. Ravikumar; M. Sharumathi; R. G. Sasikumar; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Exploring the Generalization Limits of UNet Variants in Road Extraction - T. V. Jayakumar; Deepak Mishra; M. Ramiya Anandakumar; Jai G. Singla (Journal of the Indian Society of Remote Sensing, 2026)

Reproductive biology and population dynamics of the five-lined snapper Lutjanus quinquelineatus (Bloch, 1790) from the Gulf of Mannar: implications for establishing minimum legal-size limits - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; R. G. Sasikumar; K. Karuppasamy; S. Parkavi; S. Pearlin Arul Granap (Environmental Biology of Fishes, 2026)

Assessing the Demographic Characteristics and Exploitation Status of the Torpedo Scad, Megalaspis Cordyla (Linnaeus, 1758) Along the Gulf of Mannar Coast - J. Joyson Paul; R. Durairaja; N. Jayakumar; M. Sharumathi; R. G. Sasikumar; K. Karuppasamy; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

Demographic Characteristics and Exploitation Status of the Blue Swimming Crab Portunus pelagicus (Linnaeus, 1758) Along the Palk Bay Coast, Southeast India - Pearlin Arul Granap S.; Durairaja R.; Jayakumar N.; Ranjith L.; Sudhan C.; Karuppasamy K.; Kalaiarasan M.; J. Joyson Paul; Nandhakumar M. (Thalassas: An International Journal of Marine Sciences, 2025)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

Feeding Biology and Life History Traits of Critically Endangered Stripenose Guitarfish Acroteriobatus variegatus (Nair & Lal Mohan, 1973) from the Gulf of Mannar, India: Implications for Conservation and Management - M. Kishore Kumar; N. Jayakumar; P. Jawahar; N. Neethiselvan; P. Padmavathy; K. Karuppasamy (Thalassas: An International Journal of Marine Sciences, 2025)

Length–Weight Relationship and Relative Condition Factor of 20 Carangid Fish Species from the Gulf of Mannar, Southeast Coast of India - J Joyson Paul; R Durairaja; N Jayakumar; K V. Venkataramani; Thangaraji Ravikumar; M Sharumathi; Kishore Kumar; Sanjay Chandravanshi; Adyasha Sahu; C Sudhan (Thalassas: An International Journal of Marine Sciences, 2025)

Spatio-temporal variations in the diversity and occurrence of lutjanid fish species (Family: Lutjanidae) of the Gulf of Mannar, Southeast coast of India - M. Sharumathi; N. Jayakumar; R. Durairaja; J. Joyson Paul; C. Sudhan; M. Kalaiarasan; L. Ranjith (Marine Biodiversity, 2025)

Length-Weight Relationships and Condition Factor of 15 Coastal Fish Species (Family: Lethrinidae) of the Gulf of Mannar, Southeast Coast of India - Sanjay Chandravanshi; N. Jayakumar; R. Durairaja; S. Aanand; E. Suresh; C. Sudhan; M. Kishore Kumar; Mahesh Chand Sonwal; Adyasha Sahu (Thalassas: An International Journal of Marine Sciences, 2025)

A review of the physiological effects of microgravity and innovative formulation for space travelers - Jey Kumar Pachiyappan; Manali Patel; Parikshit Roychowdhury; Imrankhan Nizam; Raagul Seenivasan; Swathi Sudhakar; M. R. Jeyaprakash; Veera Venkata Satyanarayana Reddy Karri; Jayakumar Venkatesan; Priti Mehta; Sudhakar kothandan; Indhumathi Thirugnanasambandham; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Biomimetic nanocomposite cryogel with enhanced peptide binding promotes therapeutic angiogenesis and bone regeneration - Sivashanmugam Amirthalingam; Seoyeon Kim; Dayeon Roo; Kyung Min Ryu; Jiwoon Jeong; Perrine M'Pemba Hennebert; Kyoung-Ha So; Jayakumar Rangasamy; Nathaniel S. Hwang (Chemical Engineering Journal, 2024)

Thirty-two years of smut disease status in the world’s largest sugarcane germplasm - R. Gopi; K. Chandran; A. Ramesh Sundar; R. Viswanathan; V. Jayakumar; Nisha M; B. Mahendran; Sony Jayaraman; Gireesan PP (Indian Phytopathology, 2024)

Excess feeding increases adipogenesis but lowers leptin transcript abundance in zebrafish larvae - William Andrew Thompson; Jithine Jayakumar Rajeswari; Alison C. Holloway; Mathilakath M. Vijayan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Analysis of Temporal Patterns of Ichthyofaunal Bycatch Landed Along the Thoothukudi Coast, Gulf of Mannar, India - S. Santhoshkumar; P. Jawahar; A. Srinivasan; N. Jayakumar; A. Subburaj; K. Karuppasamy; M. Srihari (Thalassas: An International Journal of Marine Sciences, 2023)

Etiology behind canine uterine inertia: Role of uterine expression of MLCK4, MYH2, and PKC genes - Magnus P.K.; Jayakumar C.; Naicy T.; Lali F.A.; Hiron M. Harshan; Abhilash R.S.; Ajithkumar S. (Animal Reproduction Science, 2023)

Multi-faceted CRISPR-Cas9 strategy to reduce plant based food loss and waste for sustainable bio-economy – A review - Palanivel Hemalatha; Ebrahim M. Abda; Shipra Shah; S. Venkatesa Prabhu; M. Jayakumar; N. Karmegam; Woong Kim; M. Govarthanan (Journal of Environmental Management, 2023)

Estimation of Size Variation and Other Biometrics in Silver Pompano Trachinotus blochii(Lacepede, 1801) Reared in Different Farming conditions - Suresh Babu P. P; Anikuttan K. K; Anuraj A; Jayakumar R; Abdul Nazar A. K; Sakthivel M; Jayasree Loka; Imelda Joseph (Thalassas: An International Journal of Marine Sciences, 2023)

Microplastics in terrestrial ecosystem: Sources and migration in soil environment - U. Surendran; M. Jayakumar; P. Raja; Girish Gopinath; Padmanaban Velayudhaperumal Chellam (Chemosphere, 2023)

Monitoring of Harmful Algal Bloom (HAB) of Noctiluca scintillans (Macartney) along the Gulf of Mannar, India using in-situ and satellite observations and its impact on wild and maricultured finfishes - Rameshkumar. P; P.S. Thirumalaiselvan; Mini Raman; L. Remya; R. Jayakumar; M. Sakthivel; G. Tamilmani; M. Sankar; K.K. Anikuttan; N. Nandini Menon; Raju Saravanan; T.T. Ravikumar; et al. (Marine Pollution Bulletin, 2023)

Impact of duration of stunting on compensatory growth and biometrics of snubnose pompano, Trachinotus blochii (Lacepede,1801) in low saline conditions - P. P. Suresh Babu; A. Anuraj; J. Loka; N. D. Praveen; K. Srinivasa Rao; M. T. Shilta; K. K. Anikuttan; R. Jayakumar; A. K. Abdul Nazar; I. Boby; J. Imelda (Thalassas: An International Journal of Marine Sciences, 2022)

Assessment of the Efficacy of Lightning Forecast Over India: A Diagnostic Study - A. Sandeep; A. Jayakumar; M. Sateesh; Saji Mohandas; V. S. Prasad; E. N. Rajagopal (Pure and Applied Geophysics, 2021)

Rice GWAS reveals key genomic regions essential for salinity tolerance at reproductive stage - Arvinder Singh Warraich; S. L. Krishnamurthy; Balwinder Singh Sooch; N. M. Vinaykumar; B. M. Dushyanthkumar; Jayakumar Bose; Parbodh Chander Sharma (Acta Physiologiae Plantarum, 2020)

Genome-wide discovery of SNPs in candidate genes related to production and fertility traits in Sahiwal cattle - M. R. Vineeth; T. Surya; Jayakumar Sivalingam; Anshuman Kumar; S. K. Niranjan; S. P. Dixit; Karanveer Singh; M. S. Tantia; I. D. Gupta (Tropical Animal Health and Production, 2020)

Spatiotemporal variation of water quality index in Kanwar wetland, Begusarai, India - Ajeet Kumar Singh; M. Sathya; Satyam Verma; S. Jayakumar (Sustainable Water Resources Management, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Isotherm and kinetic modeling of sorption of Cadmium onto a novel red algal sorbent, Hypnea musciformis - V. Jayakumar; S. Govindaradjane; M. Rajasimman (Modeling Earth Systems and Environment, 2019)

Analysis of Drought from Humid, Semi-Arid and Arid Regions of India Using DrinC Model with Different Drought Indices - U. Surendran; B. Anagha; P. Raja; V. Kumar; K. Rajan; M. Jayakumar (Water Resources Management, 2019)

Health risk assessment of heavy metals in crop grains grown on open soils of Kanwar wetland, India - Ajeet Kumar Singh; M. Sathya; Satyam Verma; S. Jayakumar (Euro-Mediterranean Journal for Environmental Integration, 2018)

Impact of climate variability on coffee yield in India—with a micro-level case study using long-term coffee yield data of humid tropical Kerala - M. Jayakumar; M. Rajavel; U. Surendran; Girish Gopinath; K. Ramamoorthy (Climatic Change, 2017)

Climate-based statistical regression models for crop yield forecasting of coffee in humid tropical Kerala, India - M. Jayakumar; M. Rajavel; U. Surendran (International Journal of Biometeorology, 2016)

Transdermal Delivery of Functional Collagen Via Polyvinylpyrrolidone Microneedles - Wenchao Sun; Mohammed Inayathullah; Martin A. C. Manoukian; Andrey V. Malkovskiy; Sathish Manickam; M. Peter Marinkovich; Alfred T. Lane; Lobat Tayebi; Alexander M. Seifalian; Jayakumar Rajadas (Annals of Biomedical Engineering, 2015)

Toxic Effects of Couroupita guianensis Against Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) - K Baskar; S Ignacimuthu; M Jayakumar (Neotropical Entomology, 2015)

Ion transport in broad bean leaf mesophyll under saline conditions - William J. Percey; Lana Shabala; Michael C. Breadmore; Rosanne M. Guijt; Jayakumar Bose; Sergey Shabala (Planta, 2014)

Sulfonylurea Receptor 1 Contributes to the Astrocyte Swelling and Brain Edema in Acute Liver Failure - A. R. Jayakumar; V. Valdes; X. Y. Tong; N. Shamaladevi; W. Gonzalez; M. D. Norenberg (Translational Stroke Research, 2014)

Endothelial-astrocytic interactions in acute liver failure - A. R. Jayakumar; M. D. Norenberg (Metabolic Brain Disease, 2013)

Complete genome sequencing and evolutionary analysis of dengue virus serotype 1 isolates from an outbreak in Kerala, South India - M. Anoop; Ashish J. Mathew; B. Jayakumar; Aneesh Issac; Sajith Nair; Rachy Abraham; M. G. Anupriya; E. Sreekumar (Virus Genes, 2012)

Processes of 30–90 days sea surface temperature variability in the northern Indian Ocean during boreal summer - J. Vialard; A. Jayakumar; C. Gnanaseelan; M. Lengaigne; D. Sengupta; B. N. Goswami (Climate Dynamics, 2012)

Processes controlling the surface temperature signature of the Madden–Julian Oscillation in the thermocline ridge of the Indian Ocean - A. Jayakumar; Jérôme Vialard; M. Lengaigne; C. Gnanaseelan; Julian P. McCreary; B. Praveen Kumar (Climate Dynamics, 2011)

Signaling factors in the mechanism of ammonia neurotoxicity - M. D. Norenberg; K. V. Rama Rao; A. R. Jayakumar (Metabolic Brain Disease, 2009)

Sensitivity of atmospheric dispersion simulations by HYSPLIT to the meteorological predictions from a meso-scale model - Venkata Srinivas Challa; Jayakumar Indrcanti; Julius M. Baham; Chuck Patrick; Monika K. Rabarison; John H. Young; Robert Hughes; Shelton J. Swanier; Mark G. Hardy; Anjaneyulu Yerramilli (Environmental Fluid Mechanics, 2008)

New concepts in the mechanism of ammonia-induced astrocyte swelling - M. D. Norenberg; A. R. Jayakumar; K. V. Rama Rao; K. S. Panickar (Metabolic Brain Disease, 2007)

Influence of the macrotidal environment on the source to sink pathways of suspended flux in the Gulf of Kachchh, India: evidence from the Ocean Colour Monitor (IRS‐P4) - O. S. Chauhan; A. A. A. Menezes; S. Jayakumar; M. A. Malik; Y. Pradhan; A. S. Rajawat; S. R. Nayak; G. Bandekar; C. Almeida; M. Talaulikar; M. V. Ramanamurty; B. R. Subramanian (International Journal of Remote Sensing, 2007)

Mechanisms of Ammonia-Induced Astrocyte Swelling - M. D. Norenberg; K. V. Rama Rao; A. R. Jayakumar (Metabolic Brain Disease, 2005)

Oxidative Stress in the Pathogenesis of Hepatic Encephalopathy - M. D. Norenberg; A. R. Jayakumar; K. V. Rama Rao (Metabolic Brain Disease, 2004)

Effect of time and mode of application of potassium on the growth, yield and quality of sugarcane ratoon - Thomas Mathew; T. M. Kurian; Babu George; Sosamma Cherian; Jessy M. Kuriakose; K. Sreekumar; G. Jayakumar (Sugar Tech, 2004)

Residual effects of sulphur nutrition on the ratoon crop of sugarcane - Thomas Mathew; T. M. Kurian; Sosamma Cherian; G. Jayakumar (Sugar Tech, 2003)

Ammonia Neurotoxicity: Role of the Mitochondrial Permeability Transition - K. V. Rama Rao; A. R. Jayakumar; M. D. Norenberg (Metabolic Brain Disease, 2003)

Butyrate inhibits proliferation-induced Proliferating Cell Nuclear Antigen expression (PCNA) in rat vascular smooth muscle cells - Kasturi Ranganna; Frank M. Yatsu; Barbara E. Hayes; Shirlette G. Milton; Armugam Jayakumar (Molecular and Cellular Biochemistry, 2000)

Differential response ofAzolla microphylla kaulf. andAzolla filiculoides Lam. to sodium fluoride - M. Eyini; K. Sujanandini; C. Pothiraj; M. Jayakumar; Bong -Seop Kil (Journal of Plant Biology, 1999)